2002
DOI: 10.1038/nbt0102-53
|View full text |Cite
|
Sign up to set email alerts
|

Production of human clotting Factor IX without toxicity in mice after vascular delivery of a lentiviral vector

Abstract: Replication-deficient lentiviral vectors (LV) have been shown to enable the stable genetic modification of multiple cell types in vivo. We demonstrate here that vascular and hepatic delivery of a third-generation HIV-derived lentiviral vector encoding human Factor IX (LV-hFIX) produced potentially therapeutic serum levels of hFIX protein with no vector-mediated local or systemic toxicity of adult mice. Portal vein administration produced the highest serum levels of hFIX and demonstrated proportionally higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…36 These levels were increased to 60% of hepatocytes by partial hepatectomy and a similar vector dose resulted in 10% hepatocyte expression of GFP in immunocompetent C57/Bl6 mice after portal vein infusion. 21 Vector dose is an important consideration for in utero gene delivery since potential hepatotoxicity could compromise fetal survival. Importantly, the dose of EIAV vector applied to fetal mice, which was similar to that delivered to the adult mice used in our study, resulted in high-level transduction of the fetus with over 90% fetal survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 These levels were increased to 60% of hepatocytes by partial hepatectomy and a similar vector dose resulted in 10% hepatocyte expression of GFP in immunocompetent C57/Bl6 mice after portal vein infusion. 21 Vector dose is an important consideration for in utero gene delivery since potential hepatotoxicity could compromise fetal survival. Importantly, the dose of EIAV vector applied to fetal mice, which was similar to that delivered to the adult mice used in our study, resulted in high-level transduction of the fetus with over 90% fetal survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lentiviruses that can infect nondividing cells 18 have been shown to provide more efficient gene transfer and sustained gene expression in vivo. 20,21 MLV-based vectors have been applied by intratracheal, intrahepatic, and intraperitoneal injection to fetal sheep and rats; 18,[22][23][24][25] however, only low levels of transgene expression were observed in all cases. Intraperitoneal vector injection to fetal sheep at 60 days of gestation resulting in marker gene expression in haematopoietic cells until at least 40 months was attributed both to the expression from an integrating vector system as well as to the induction of immune-tolerance against the transgenic protein.…”
Section: Introductionmentioning
confidence: 99%
“…A study with a VSV-G-pseudotyped HIV-1 vector expressing human Factor IX (hFIX) demonstrated circulating levels of the recombinant protein in the order of 10-100 ng/ml after administration of 2 Â 10 8 TU into either nude or immunocompetent mice. Levels of hFIX reduced more rapidly in the immunocompetent mice compared to the nude mice, 35 possibly due to the induction of an immune response against the transgene product. The explanation that the reduction in transgene product is due to clearance of expressing cells by the immune system is underlined by a recent study monitoring both hFIX and GFP expression by HIV-based lentivectors.…”
Section: Eiav Vector For Systemic Delivery Of Proteinsmentioning
confidence: 96%
“…33,34 Discussion Previous evaluation of HIV-1 lentivectors following systemic delivery have demonstrated long-term expression of the transgene for up to 1 year, depending on the transgene and host. [33][34][35] An alternative to HIV-1 is the EIAV-based vector, which has been developed, in part, because HIV-1 is a human pathogen and as a result may face extra hurdles in clinical use. In addition to this, the potential advantages of EIAV are its relative simplicity compared to HIV-1, the inability of the parent virus to replicate in human cells and the nonlethal nature of the infection in its natural host, the genus Equidiae.…”
Section: Eiav Vector For Systemic Delivery Of Proteinsmentioning
confidence: 99%
“…Lentiviral vectors are retroviral vectors, which, in some instances, have been shown to be able to transduce low-or nonproliferating cells such as neurons, nonstimulated normal hepatocytes or growth-arrested HCC cells conversely to MLV-derived vectors. [49][50][51][52][53][54][55] MLV-derived vectors and HIV-1-derived vectors share several features. The gag, pol and env coding sequences, along with the rev, vpr, nef, vif, vpu and tat coding sequences which encode regulatory and accessory proteins, have been eliminated from the vector backbone.…”
Section: Viral Vectorsmentioning
confidence: 99%